The growing challenge of youth unemployment in Europe and America : a cross-cultural perspective - Jagannathan, Radha (Bristol University Press, 2021)
This book provides a culturally nuanced analysis of key issues relating to youth unemployment. Examining the causes and consequences of youth unemployment, it assesses ways forward to promote economic self-sufficiency.